Indicators in Environmental Health: Identifying and Selecting Common Sets - Eyles, John (Can J Public Health, 2002)
In association with the proposed goals of the conference, this paper is presented to support the conference discussions on environmental health indicators by providing background on indicators for environmental health and their identification, selection, organization and use. This paper discusses the purpose of indicator use, frameworks used to organize indicators and the common types of indicators in use in monitoring programs today. It proposes a process for the identification and selection of indicators within the different environments, stressing the importance of clear goal definition and scientific and use-based criteria selection to support decisions. Finally, the paper suggests methods by which to organize and limit the number of indicators retained within a program, and the development of a potential “core” of indicators common to many environments and geographical scales.